Entre la coronació de Ramon Berenguer IV i la dotalia de Catalunya. Edició crítica del ms. 280 de la Biblioteca de Catalunya. - IBORRA, JOAN (Scripta, 2015)
This XVI century codec gathers six texts from varied sources without any chronological criterion. The document consists of extracts copied from other medieval chronicles that links interesting contact points with the Crónica i dietari del capellà d'Alfons el Magnànim, the ms. d.III.2 of El Escorial by Martí de Viciana el Vell -- grandparent of the historian -- and the Sumari d'Espanya by Berenguer de Puigpardines.